(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
In recent decades, digitalization has permeated all spheres of life—from work to personal relationships. However, the rapid development of technology has also introduced new challenges, notably digital isolation. This condition refers to a state in which an individual loses the ability for full social interaction with others and society, becoming dependent on digital technologies. The term "technological autism" is often used in this context to describe disruptions in social behavior resulting from the persistent use of digital devices. Digital isolation is characterized by a progressive detachment from the real world, with increased immersion in digital devices and online interactions. This phenomenon is associated with frequent use of smartphones, social networks, and other digital tools, leading to decreased activity in offline environments. Individuals in this state often report feelings of emotional emptiness and alienation despite maintaining virtual contacts.